THE CHARACTERISTIC OF BEEHIVE TREE AND THE PREFERENCE OF BEE NESTING IN THE BEEHIVE SURROUND FORESTOFGUNUNG SAHILAN VILLAGE, GUNUNG SAHILAN DISTRICKAMPAR REGENCY, RIAU PROVINCE - Ika Gussuwana; Defri Yoza; M. Mardhiansyah ' (Fakultas Pertanian, Universitas Riau, 2017)
The beehive surround forest is one of the Apis dorsata’s habitat. One of the beehive surround forest lies in Gunung Sahilan village, Gunung Sahilan district, Kampar regency, Riau province. However beehive tree less manage by local community, so that the honey’s bee from Apis dorsata more difficult to find. This research aimed to identify the species and the characteristic of beehive tree and know the preference of bee nesting in the beehive surround forest of Gunung Sahilan village. This research using purpossive sampling technique and descriptive analysis. The research results showed that the species of beehive tree in the beehive surround forest of Gunung Sahilan village is Gluta renghas Linn and Artocarpus maingayi King with the characteristic of beehive tree is wide and open canopy and dome shaped, the bark of the branch is doesn’t break and peeling, the oblique angle of the branch is under 40o with sympodial branching system. While the preference of bee nesting in the beehive surround forest of Gunung Sahilan village is Gluta renghas Linn with the quantity of nests per tree is 21 nests, high more than 40 meters and a diameter of between 100-200 cm, wide and open canopy, the oblique angle of the branch of between 20o-40o, sympodial branching system and medium sized leaves.